PERCEIVED SOCIAL SUPPORT AND LOCUS OF CONTROL OF ADOLESCENTS IN NATURAL DISASTER AFFECTED AREA OF KERALA - Joseph, Abhilash; Sharma, Megha Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Natural disasters can profoundly affect adolescents, disrupting their psychological and social development. This study explores the relationship between perceived social support and locus of control among adolescents in natural disaster-affected areas of Kerala, India. Data were collected from 600 adolescents aged 16–20 years residing in districts severely impacted by natural calamities such as floods and landslides. A quantitative approach was employed, utilizing standardized questionnaires to assess the extent of perceived social support and locus of control. Results indicate that higher levels of social support correlate strongly with an internal locus of control, which is associated with better emotional resilience and coping mechanisms. The study also found that there is a gender difference in perceived social support and locus of control with male adolescents exhibit higher social support thereby internal locus of control than female adolescents.